Factors associated to the notification of congenital syphilis: an indicator of quality of prenatal care - Inacia Sátiro Xavier de França; Joana D’arc Lyra Batista; Alexsandro Silva Coura; Cibely Freire de Oliveira; Andressa Kaline Ferreira Araújo; Francisco Stélio de Sousa (Rev Rene)
Objective: to analyze factors associated to the notification of congenital syphilis. Methods: a cross-sectional documentary, quantitative study, made through the National System of Notifiable Diseases. The study consisted of 113 notified cases. A data collection form was used and Chi-square and Fisher tests were made. Results: women had prenatal exams (80.2%), serologic testing before six months of pregnancy (46.7%) and after (53.3%). There was an association for the variables race (p = 0.005) and serological test (p = 0.044). The treatment of the pregnant woman was inadequate (64.5%) and the partner was not treated (85.7%). Conclusion: it was found that the number of cases is growing, increasing the possibility of children with severe sequelae. So improvements in prenatal care are still needed.